Fertility Desires and Intentions of HIV-Positive Women of Reproductive Age in Ontario, Canada: A Cross-Sectional Study - Loutfy, Mona R. (Public Library of Science, 2009)
BACKGROUND: Improvements in life expectancy and quality of life for HIV-positive women coupled with reduced vertical transmission will likely lead numerous HIV-positive women to consider becoming pregnant. In order to clarify the demand, and aid with appropriate health services planning for this population, our study aims to assess the fertility desires and intentions of HIV-positive women of reproductive age living in Ontario, Canada. METHODOLOGY/PRINCIPAL FINDINGS: A cross-sectional study with recruitment stratified to match the geographic distribution of HIV-positive women of reproductive age (18–52) living in Ontario was carried out. Women were recruited from 38 sites between October 2007 and April 2009 and invited to complete a 189-item self-administered survey entitled “The HIV Pregnancy Planning Questionnaire” designed to assess fertility desires, intentions and actions. Logistic regression models were fit to calculate unadjusted and adjusted odds ratios of significant predictors of fertility intentions. The median age of the 490 participating HIV-positive women was 38 (IQR, 32–43) and 61%, 52%, 47% and 74% were born outside of Canada, living in Toronto, of African ethnicity and currently on antiretroviral therapy, respectively. Of total respondents, 69% (95% CI, 64%–73%) desired to give birth and 57% (95% CI, 53%–62%) intended to give birth in the future. In the multivariable model, the significant predictors of fertility intentions were: younger age (age<40) (p<0.0001), African ethnicity (p<0.0001), living in Toronto (p = 0.002), and a lower number of lifetime births (p = 0.02). CONCLUSIONS/SIGNIFICANCE: The proportions of HIV-positive women of reproductive age living in Ontario desiring and intending pregnancy were higher than reported in earlier North American studies. Proportions were more similar to those reported from African populations. Healthcare providers and policy makers need to consider increasing services and support for pregnancy planning for HIV-positive women. This may be particularly significant in jurisdictions with high levels of African immigration.